In vivo Assessment of Cold Atmospheric Pressure Plasma Technology on the Bioactivity of Spirulina - Pina-Pérez, María Consuelo; Úbeda-Manzanaro, María; Beyrer, Michael; Martínez, Antonio; Rodrigo, Dolores (Frontiers in Microbiology, 2022)
The present study challenges the in vivo assessment of cold atmospheric pressure plasma (CAPP) technology on the bioactive activity (antioxidant/antiaging and antimicrobial potential) of Spirulina powder, using Caenorhabditis elegans as an animal model. Surface microdischarge cold atmospheric pressure plasma (SMD-CAPP) treatment was 3.3 W discharge power for 7 min. C. elegans lifespan and egg laying were used as indicators of antioxidant/antiaging potential of Spirulina (1 mg/mL), when grown with Spirulina CP-treated [E_SCP] and untreated [E_S], compared with a control [E_0] (non-supplemented with Spirulina). According to our results, under both Spirulina supplemented media [E_SCP and E_S] and for the first 17 days, nematodes experienced an increase in lifespan but without significant differences (p>0.05) between control and Spirulina CP-treated. Regarding the in vivo assay of the antimicrobial potential of Spirulina against Salmonella enterica serovar Typhimurium (infected worms), no significant differences (p-value > 0.05) were found between the three exposure scenarios (control [S_0]; Spirulina supplemented media [S_S]; CP-treated Spirulina supplemented media [S_SCP]). According to present results, CAPP-treatment do not influence negatively the lifespan of C. elegans but a reduction in the Spirulina antiaging potential was found. No in vivo modifications in antimicrobial activity seem to be linked to CAPP-processed Spirulina.